DESAIN DAN IMPLEMENTASI UI/UX KURSUS PROGRAMMING ONLINE DENGAN PENDEKATAN ERGONOMI BERBASIS MOBILE - Rasmila, Rasmila; Sutabri, Tata; Adila, Nia (Universitas Nusa Cendana, 2023)
The development of the higher education sector and the large number of unemployment rates in Indonesia require that students and alumni of each institution have the expertise they have mastered with UI (User Interface) / UX (User Experience) technology-based design and implementation that will always make everything effective and efficient. on products or applications that have become a trend to be carried out at this time. Simply put, the UI/UX discipline has the goal of building something that makes a system more user friendly so it can function properly which makes a product more valuable. With so many students and alumni from several agencies, namely in the field of information technology education, this provides a great opportunity to be more able to innovate with various new technologies such as mobile-based learning applications and online courses. This research aims to focus on the discipline of user ergonomics, namely how the behavior and habits of users such as the pattern of the user's fingers when using the application and provide attractive visual colors, the location of buttons that are easy to reach, typefaces that are easy to read and easy to understand. as well as providing convenience for users of these applications, so as to see and assess the design and implementation of UI/UX applications for online programming courses, so that designs can be evaluated and can strengthen opportunities to implement better applications for users, especially students and alumni of higher education institutions in the field information Technology. The method to be used is UCD (User Centered Design) which consists of 4 stages, namely, Specify Understand Context of Use, Specify User Requirements, Design Solutions, and Evaluate Against Requirements and the method for implementing applications uses the waterfall model. The results of this study show how the design and implementation of a mobile-based online programming course application is named